ANALISIS MINAT PEMERINTAH DAERAH MENEMPATKAN DANA DAERAH PADA BANK SYARIAH - Syukrilah, Muhamad Djedjen; Trihantana, Rully; Kusumaningrum , Ria (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
The Regional Government of Pamijahan, Cibungbulang and Ciampea Districts, Bogor Regency, has an increasing desire to place its funds in sharia banks. Using descriptive quantitative research methods, and using multiple linear regression data analysis techniques, the research results show that the Regional Government Regulation variable has no effect on regional government interest in placing regional funds in Islamic banks. With a calculated T value of 3.747 > T table 2.04841 and a significance level of 0.002 <0.05, the Regional Government of the sub-districts, namely Pamijahan, Cibungbulang, and Ciampea, Bogor Regency has an interest in placing regional funds in sharia banks, especially because of the Nisbah factor. Profit Sharing in Sharia Banks. The research results also show that simultaneously the variables Religiosity, Knowledge, Government Regulation, Promotion, Existence of Facilities, Administrative Costs, and Profit Sharing Ratio have a significant effect on the Regional Government's interest in placing regional funds in Islamic banks.